2016
DOI: 10.21037/tau.2016.08.11
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement therapy and voiding dysfunction

Abstract: Testosterone replacement therapy (TRT) represents an increasing popular treatment option for men with late-onset hypogonadism (LOH). Because of unsubstantiated beliefs of testosterone’s effect on the prostate, the FDA has recently placed a warning on testosterone products, stating that TRT may worsen benign prostatic hyperplasia (BPH). Within this review article we have demonstrated the current understanding of the physiology of testosterone and its relationship with prostatic and lower urinary tract physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…In fact, recent reviews suggested testosterone may be beneficial for BPH/LUTS, possibly by increasing the expression and activity of nitric oxide synthase to achieve smooth muscle relaxation [38]. Testosterone deficiency may be a risk factor for BPH/ LUTS, suggesting a causal relationship between hypogonadism and the occurrence of BPH/LUTS [39]. A concern remains that testosterone therapy (TTh) may worse may worsen LUTS in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent reviews suggested testosterone may be beneficial for BPH/LUTS, possibly by increasing the expression and activity of nitric oxide synthase to achieve smooth muscle relaxation [38]. Testosterone deficiency may be a risk factor for BPH/ LUTS, suggesting a causal relationship between hypogonadism and the occurrence of BPH/LUTS [39]. A concern remains that testosterone therapy (TTh) may worse may worsen LUTS in patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, preliminary evidence indicates that men with LUTS benefit from T treatment [ 116 ] and pilot studies have also shown that T therapy has a positive effect on LUTS men with TD [ 140 ]. In a recent review Baas and Köhler [ 150 ] suggested that T may be beneficial for BPH/LUTS, likely via increased expression and activity of nitric oxide synthase concomitant with smooth muscle relaxation. Concern remains that T therapy may worsen LUTS secondary to BPH, although few major adverse events have been reported with T treatment.…”
Section: Does Testosterone Therapy Improves Lower Urinary Tract Symptmentioning
confidence: 99%
“…This mechanism of T-induced NO smooth muscle relaxation is also reflected in the effect of phosphodiesterase-5 (PDE-5) inhibitors used as effective treatment of LUTS/BPH. While PDE-5 interacts with NOS with the effect to reduce NO production, the use of PDE-5 inhibitors consequently leads to an up-regulation of NO production [ 1 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of T in the lower urinary tract suggests a physiological correlation between T and LUTS. Lack of T may be a risk factor for LUTS/BPH suggesting a causal link between hypogonadism and incidence of LUTS/BPH [ 11 ].…”
Section: Introductionmentioning
confidence: 99%